2018
DOI: 10.1016/j.juro.2018.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Elastic and Rigid Registration during Magnetic Resonance Imaging/Ultrasound Fusion-Guided Prostate Biopsy: A Multi-Operator Phantom Study

Abstract: We found no difference in registration errors between rigid and elastic registration overall but rigid registration decreased the registration error of targets near the prostate edge. Additionally, operator experience reduced registration errors regardless of the registration method. Therefore, elastic registration algorithms cannot serve as a replacement for attention to detail during the registration process and anatomical landmarks indicating accurate registration when beginning the procedure and before tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
22
0
3
Order By: Relevance
“…Fourth, there might be an error as a result of the fusion of MRI and US. It is estimated that the error of the puncture is within 5 mm . Fifth, it is difficult to completely eliminate the potential bias in a simple comparison of TB and SB by our method.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Fourth, there might be an error as a result of the fusion of MRI and US. It is estimated that the error of the puncture is within 5 mm . Fifth, it is difficult to completely eliminate the potential bias in a simple comparison of TB and SB by our method.…”
Section: Discussionmentioning
confidence: 90%
“…It is estimated that the error of the puncture is within 5 mm. 29,30 Fifth, it is difficult to completely eliminate the potential bias in a simple comparison of TB and SB by our method. Regions of 10-core SB were performed not to be affected by targeted lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Fusion biopsy is based on the assumption that registration between ultrasound and MRI is inherently accurate and dynamically sustained during the procedure. In practice, differences in prostatic outlining between modalities may result in erroneous baseline registration, and movement of the ultrasound transducer during the procedure may cause motion and deformation of the prostate resulting in registration error and false negative biopsy results [24]. While fusion biopsy is established as having better diagnostic performance than systematic biopsy [4][5][6][7][8][9], our findings suggest in-bore biopsy may be better still.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Based on experiments on a phantom, these two registration methods perform similarly, except at the edges where rigid registration seems to be more accurate. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Notably, in the previously described phantom study comparing the performance of registration algorithms, the impact of operator experience on registration error was more significant than that of the type of algorithm employed. 27 Meng et al found a significant institutional learning curve with MRI-TRUS fusion targeting, increasing the cancer detection rate in PI-RADS 4/5 lesions on MRI by 26% over 4 years. 29 Similar learning curves likely also apply to both the interpreting radiologist and pathologist.…”
Section: Introductionmentioning
confidence: 99%